Direct and indirect measurement of large electrocaloric effect in B2O3-ZnO glass modified Ba0.65Sr0.35TiO3 bulk ceramics. (1st March 2021) - Wang, Shi-Bin; Dai, Guang-Zhou; Yao, Ying-Bang; Zhao, Xiao-Bo; Tao, Tao; Liang, Bo; Lu, Sheng-Guo
Graphical abstract: Image, graphical abstract Abstract: Barium strontium titanate (Ba0.65 Sr0.35 TiO3 -BST) added with a 0.5 wt% of B2 O3 -ZnO glass phase was prepared via a solid-state reaction approach. The lattice structures and morphologies of the ceramics were analyzed using X-ray diffraction and scanning electron microscopy technologies. The dielectric and ferroelectric properties of the glass added BST ceramics were characterized using a precision impedance analyzer and a ferroelectric polarization-electric field (P-E) hysteresis loop tester, respectively. The electrocaloric effect (ECE) was directly measured by a computer controlled thermocouple and high-voltage power supply, and also indirectly calculated using the Maxwell relation and the polarization extracted from the P-E loops as a function of temperature and electric field. The results indicate that when added with 0.5 wt% of B2 O3 -ZnO glass phase, the breakdown electric field of BST ceramic can be increased, and the adiabatic temperature change ΔT was enhanced from 1.70 K to 2.29 K.